Integrated genomic profiling identifies microRNA‐92a regulation of IQGAP2 in locally advanced rectal cancer. Issue 4 (April 2016) - Pelossof, Raphael; Chow, Oliver S.; Fairchild, Lauren; Smith, J. Joshua; Setty, Manu; Chen, Chin‐Tung; Chen, Zhenbin; Egawa, Fumiko; Avila, Karin; Leslie, Christina S.; Garcia‐Aguilar, Julio
Abstract : Locally advanced rectal cancer (LARC) is treated with chemoradiation prior to surgical excision, leaving residual tumors altered or completely absent. Integrating layers of genomic profiling might identify regulatory pathways relevant to rectal tumorigenesis and inform therapeutic decisions and further research. We utilized formalin‐fixed, paraffin‐embedded pre‐treatment LARC biopsies (n=138) and compared copy number, mRNA, and miRNA expression with matched normal rectal mucosa. An integrative model was used to predict regulatory interactions to explain gene expression changes. These predictions were evaluated in vitro using multiple colorectal cancer cell lines. The Cancer Genome Atlas (TCGA) was also used as an external cohort to validate our genomic profiling and predictions. We found differentially expressed mRNAs and miRNAs that characterize LARC. Our integrative model predicted the upregulation of miR‐92a, miR‐182, and miR‐221 expression to be associated with downregulation of their target genes after adjusting for the effect of copy number alterations. Cell line studies using miR‐92a mimics and inhibitors demonstrate that miR‐92a expression regulates IQGAP2 expression. We show that endogenous miR‐92a expression is inversely associated with endogenous KLF4 expression in multiple cell lines, and that this relationship is also present in rectal cancers of TCGA. Our integrative model predicted regulators of gene expression change in LARC using pre‐treatment FFPE tissues. Our methodology implicated multiple regulatory interactions, some of which are corroborated by independent lines of study, while others indicate new opportunities for investigation. © 2016 Wiley Periodicals, Inc.